THU0588 Reduction in the utilisation of prednisone and/or methotrexate following the initiation of etanercept in paediatric patients. (12th June 2018) - Khraishi, M.; Millson, B.; Woolcott, J.; Jones, H.; Marshall, L.
Abstract : Background: In Canada, the paediatric indications of the soluble TNFα receptor etanercept (ETN) are active ankylosing spondylitis (AS) and moderate to severely active juvenile idiopathic arthritis (JIA; in those who have had an inadequate response to ≥1 disease-modifying anti-rheumatic drugs and are ≥4 years of age). A previous analysis of Canadian claims data for children demonstrated a 78% yearly retention rate over Year 1 for ETN, which remained high over Years 2–6 (80%–90% per year). However, at this time, the changes in co-medication during ETN treatment in paediatric patients have rarely been evaluated in the real-world setting. Objectives: To evaluate co-treatment utilisation and ETN costs in Canadian paediatric patients initiating ETN therapy. Methods: A retrospective cohort study was conducted using longitudinal prescription drug claims data from the IQVIA Private Drug Plan (PDP), Ontario Public Drug Plan (OPDP), and Quebec Public Drug Plan database (RAMQ). Biologic-naïve paediatric patients (<18 years, with no biologic treatment in the preceding 12 months) were included if they initiated ETN during the selection period Jan 2008-Jan 2016). Disease indications were inferred through patient drug history. Analyses of ETN doses and co-treatments were conducted in patients<17 years at index and with no missing data or drug histories indicative of conditions other than JIA, AS, or psoriatic arthritis (PSA). Weekly ETN dose was estimated for patients who completed 12 month continuous ETN therapy (7 x [mg dispensed/days between claims]). Co-treatments were captured for the 6 months preceding and 12 months following index. Drug costs of ETN (manufacturing plus wholesale and pharmacy mark-up) were estimated for all those <18 years who initiated ETN therapy. Results: The study identified 391 patients<18 years old who initiated ETN and who had not received treatment with a biologic in the preceding 12 months. From this group 330 patients provided data for the evaluation of ETN doses and co-treatments (67% female, 39% aged 10–14 years). The majority were from Quebec (36%) or Ontario (33%), insured on PDP (87%). Drug history was consistent with JIA (96%), PSA (3%), and AS (1%). Among the 316 patients who completed 12 months of continuous ETN therapy, the average weekly ETN dose was 31 mg (range 29–35 mg), but varied with age. Overall, 103 of 330 patients (31%) used methotrexate (MTX) before initiating ETN, with 85/103 (83%) continuing this through the first 12 months of treatment; 28% of patients (n=92) used prednisone (PRD) before initiating ETN, with 46/92 (50%) continuing PRD during the first 12 months of ETN treatment. In patients continuing co-treatment, weekly dosages were significantly reduced (p≤0.008 by paired t -test; figure 1). The average yearly cost of ETN among the 330 paediatric patients indexed was 13 671 (Canadian per year). Conclusions: This evaluation of Canadian claims data demonstrated that less than a third of paediatric patients initiating ETN were co-treated with MTX or PRD. Many patients discontinued their co-therapies, and among those who continued therapy with these agents, weekly dosages of MTX or PRD were significantly lower within the first year of initiating treatment with ETN. Reference: [1] Khraishi M, et al. Arthritis Rheumatol2017;69:S10. Disclosure of Interest: M. Khraishi Consultant for: Pfizer, Canada and Amgen, Canada, B. Millson Employee of: IQVIA, J. Woolcott Shareholder of: Pfizer, Employee of: Pfizer, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, L. Marshall Shareholder of: Pfizer, Employee of: Pfizer